2001
DOI: 10.1111/j.1530-0277.2001.tb02148.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Availability and Injury: The Role of Local Outlet Densities

Abstract: Background:We analyzed the relationship between alcohol availability and injury that occurred during the 6 months before survey administration.Method: The data examined were from a general population survey administered to 13,440 California respondents as part of a community-based project to reduce alcohol-involved injury and death. Two separate analyses were performed. The first considered individual local outlet densities (which included both on-premise establishments such as bars and restaurants and off-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Measures of availably of alcohol have been found to predict drinking and related problems in adults. 26,27,28 More recently alcohol outlet density has been related to ease of underage purchase of alcohol 29 and to frequency of underage drinking and driving and riding with drinking drivers. 30 In the only currently published experimental study addressing changes in availability on youth drinking, 24 it was found that while a comprehensive environmentally focused program, which included enforcement of sales laws as one of several components, led to increases in checking age-identification by alcohol merchants and reduced sales to minors, it had no observed effects on drinking by high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of availably of alcohol have been found to predict drinking and related problems in adults. 26,27,28 More recently alcohol outlet density has been related to ease of underage purchase of alcohol 29 and to frequency of underage drinking and driving and riding with drinking drivers. 30 In the only currently published experimental study addressing changes in availability on youth drinking, 24 it was found that while a comprehensive environmentally focused program, which included enforcement of sales laws as one of several components, led to increases in checking age-identification by alcohol merchants and reduced sales to minors, it had no observed effects on drinking by high school students.…”
Section: Introductionmentioning
confidence: 99%
“…However, alcohol availability (measured by access to shops and restaurants which sell alcohol) may help to explain the link between neighbourhood deprivation and harmful alcohol consumption. Neighbourhood deprivation has been associated with the number of alcohol outlets, with more outlets in poorer areas; and studies have shown that a higher density of alcohol outlets is associated with increased rates of youth drinking and driving, assault, violence and homicide, rates of injury and rates of traffic collisions and traffic injuries (Scribner et al 1994, 235 1995; 236 Treno et al, 2001; 237 Gruenewald et al, 2002 238 ). Studies at the city level, mainly in North America, have suggested that the density of alcohol outlets may be higher in poorer neighbourhoods (Pollack et al, 2005 239 ).…”
Section: Competing Tensions In Shaping Public Health Interventionsmentioning
confidence: 99%
“…While the body of outlet density research suggests that, overall, outlet density is positively associated with a range of harms; there are variations across the literature depending on location, geographic unit and type of outlet (on‐site outlets including bars and restaurants, and off‐site outlets such as liquor stores) 3,5,10,47,48 . This study suggests that analysing the data for an entire city together may mask or, at the least, attenuate associations that exist in a specific part of the city, and that future research in this area should take these differences into account.…”
Section: Discussionmentioning
confidence: 80%